Targeting unimolecular G-quadruplex nucleic acids: a new paradigm for the drug discovery?. (October 2014) - Parrotta, Lucia; Ortuso, Francesco; Moraca, Federica; Rocca, Roberta; Costa, Giosuè; Alcaro, Stefano; Artese, Anna
<x xml:space="preserve">Abstract</x> Introduction: G-quadruplexes (G4s) are targets of great interest because of their roles in crucial biological processes, such as aging and cancer. G4s are based on the formation of G-quartets, stabilised by Hoogsteen-type hydrogen bonds and by interaction with cations between the tetrads. These biologically relevant conformations were first discovered in eukaryotic chromosomal telomeric DNA, but have also been found in the proximal location of promoters in a number of human genes. Therefore, the extensive analysis of an intriguing target could move towards the rational drug design of new selective anticancer agents. Areas covered: The authors review G4 structural characterisation, with detailed insight related to the polymorphism issue. The authors describe the topologically distinct G4 structural forms and the factors involved in their interconversion mechanisms, such as the sequence of the oligonucleotides, the strand stoichiometry and orientation, the syn–anti conformation of the guanine glycosidic bonds and the G4 loop types and the environmental factors. Furthermore, the authors report several studies related to folding and unfolding kinetic profiles in order to understand the conformational view of monomolecular G4 formations. Expert opinion: G4 unimolecular nucleic acids can be considered as valid targets for the rational drug development of novel anticancer agents. Structural biology represents an essential link between the biology and medicinal chemistry knowledge in this field. Insilico methods have already been demonstrated to be useful, especially if well integrated with biophysical tests. If this proves successful, the G4-targeting paradigm could also be extended to drug discovery beyond neoplastic pathologies.